Should organizing premier-level European football be a monopoly? And who should run it? - An economists' perspective - Oliver Budzinski; Arne Feddersen (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2022)
The controversy around the breakaway European Super League, set to conquer the UEFA Champions League, and the surrounding antitrust proceedings revive the academic discussion about the monopoly power of sport-internal governing bodies (like the UEFA), the justification for and limits of their powers, and potential abuses of their power. Against this background, we discuss how much monopoly is unavoidable in premier-level European football and how its powers can be limited and, thus, scope and incentives for power abuse may be reduced. We particularly find that championship management can be periodically assigned to third-parties (like the Super League organizers) by tender procedures, thus, creating a periodical competition for the market, fueling innovation incentives and strengthening the influence of fans' preferences.
Keywords: D02; D42; D47; K21; L12; L30; L40; L83; Z20; 330; sports economics; Super League; UEFA Champions League; monopoly; marketpower; sport associations; rival leagues